The Influence of Price and Product Quality on Consumer Decisions in Purchasing Zara Brand Clothing in Medan 2024 - Purba, Esteria; Manik, Levinesya; Khan, Zalfasya Thurfahindi; Sembiring, Putri Sosanti (Generasi Sains Indonesia, 2025)
This study investigates the influence of price and product quality on consumer purchasing decisions for Zara brand clothing in Medan in 2024. The rapid development of the fashion industry in Indonesia and the increasing presence of global fast-fashion brands such as Zara have made it important to understand how local consumers evaluate their choices. Employing a quantitative research design, the study used a purposive sampling technique with 100 respondents who had previously purchased Zara products in Medan. Primary data were gathered through structured questionnaires and analyzed using multiple linear regression with the aid of SPSS. The analysis revealed that both price and product quality exert a positive and significant effect on consumer purchasing decisions. While price remains a critical consideration, product quality emerged as the dominant factor influencing satisfaction, loyalty, and repurchase intention. These findings underscore the importance for Zara’s management to maintain a consistent balance between competitive pricing and high-quality standards. Strategically aligning price fairness with superior product quality is expected to strengthen consumer trust, increase purchase frequency, and enhance Zara’s competitiveness in the Medan fashion market.